Siegeslieder - Pindar.,Bremer, Dieter (De Gruyter, Inc., 2011)
Intro – Title Page – Copyright – Inhalt – ZUM VERSTÄNDNIS – BIBLIOGRAPHISCHE HINWEISE.
Description based on publisher supplied metadata and other sources
Keywords: Pindar – Translations into German; Laudatory poetry; Greek – Translations into German; Odes; Greek – Translations into German